Trinidad and Tobago : Selected Issues, Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper and Statistical Appendix reviews developments in the energy sector of the Republic of Trinidad and Tobago during 1997-99, and assesses the outlook for energy-related industries. The paper highlights that in 1998, the decline of mature fields was exacerbated by the low price of oil experienced during the year, which made exploitation of some fields uneconomic. The paper examines the fiscal sustainability of energy resources. It also analyzes trade liberalization that has been an integral part of Trinidad and Tobago's efforts to restructure its economy for sustained growth.